Penyuluhan dan Sosialisasi Kesehatan Pelaksanaan K3 Dalam Pelayanan Kesehatan - Poetra, Ricky Perdana (STIKES Yayasan RS.Dr.Soetomo, 2023)
Health services are activities that must be considered to protect patients. however, the occupational safety and health of health workers, especially in the community, also needs to be improved. the methods used in this counseling are lectures and distribution of pre-post test. The result of this extension activity is an increase in public knowledge regarding occupational safety and health in health services. It is suggested to the local government to carry out practicum in the introduction and use of personal protective equipment in providing health services to the community